Intervenciones de enfermería y su relación con las complicaciones de ulcera en pie diabético en pacientes Atendidos En El Hospital General Guasmo Sur En El Primer Semestre Del 2018 - Banchon Peña, Eloy Jacinto (2018)
The objective of this research is to determine the relationship between nursing interventions and diabetic foot ulcer complications in patients treated at the Guasmo Sur General Hospital in the first semester of 2018. The deductive, descriptive methodology was applied. field, quantitative, with use of the survey to the nursing professionals and patients with diabetic foot, obtaining the following results: It was identified that the majority of patients are over 50 years of age, belonging to the male sex, did not use the appropriate footwear, nor did they perform frequent physical activity, who did not feel totally satisfied with the nursing professionals, because they did not provide self-care talks; The main risk factor associated with diabetic foot complications was the lack of specialized counseling for self-care of the lower extremities; Nursing interventions that were performed properly, were the taking of vital signs, washing of hands prior to healing the wound, administration of medication at the right time, postural changes and the healing of lacerated wounds for lack of prevention, among the most important. In conclusion, the main limitations were the lack of counseling and self-care talks related to diet, care of the lower extremities and glycemic control.